Impact origin of pink spinel in the Chang’e-6 lunar soils - Linxi Li; Guangyuan Yu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Lihui Jia; Di Zhang; Shitou Wu; Guoqiang Tang; Hao Wang; et al. (Geochimica et Cosmochimica Acta, 2026)

Ejecta from Chaffee S Crater in Chang’E-6 Landing Site Constrained by Seifertite-Bearing Norite - Zhan Zhou; Sen Hu; Yubing Gao; Linxi Li; Huicun He; Liang Gao; Mengfan Qiu; Lixin Gu; Xu Tang; Xiaoguang Li; Wei Yang; Yangting Lin; et al. (Journal of Earth Science, 2026)

Anthropogenic disturbances drive stepwise geomorphic changes of shoal-channel systems in a tide-dominated estuary - Ping Zhang; Linxi Fu; Xiangyuan Li; Jianliang Lin; Huayang Cai; Zhijun Dai; Qingshu Yang (Marine Geology, 2026)

Delivery of carbonaceous materials to the Moon - Linxi Li; Mengfan Qiu; Sen Hu; Hejiu Hui; Yi Chen; Qiu-Li Li; Wei Yang; Yuyang He; Shitou Wu; Hao Wang; Guoqiang Tang; Di Zhang; et al. (Icarus, 2026)

Spring-neap variations in tidal duration asymmetry in the Pearl River Estuary: Dominant tidal combinations and long-term evolution - Jianliang Lin; Shuai Hu; Ping Zhang; Linxi Fu; Xianzhao He; Huayang Cai; Lixia Niu; Xiaohe Zhang; Qingshu Yang (Journal of Hydrology, 2025)

The evolution and morphodynamic characteristics of shoals and troughs in Lingdingyang Bay of the Pearl River Estuary - Linxi Fu; Yuhang Zhong; Ping Zhang; Lixia Niu; Xiaohe Zhang; Jianliang Lin; Huayang Cai; Qingshu Yang (Frontiers in Marine Science, 2025)
Shoals and troughs are the fundamental geomorphological units of estuarine systems. However, their definition and morphodynamic characteristics, influenced by the complex dynamic environment, remain a critical challenge. This work introduces a depth–area spatial function as a quantitative criterion for the definition of shoals and troughs, while simultaneously elucidating their geodynamic implications. The Lingdingyang Bay (LDB) of the Pearl River Estuary serves as a case study. From 1901 to 2018, the LDB consisted of the West Shoal, Middle Shoal, and East Shoal and the West Trough and East Trough. The threshold depth of the LDB shifted from −5.75 m in 1901 to −4.75 m between 1964 and 2018. The depth–area distribution curve of the LDB exhibits two dominant peak depths (approximately 0 m and −2 m) within the shoal stable state, which categorizes shallow areas into high, medium and low tidal flats. The shoal–trough area ratio in the LDB, relative to the threshold depths, increased from 1901 to 1998, followed by a decline between 2008 and 2018, and culminated in a restoration to the level seen in 1901 (65% shoals and 35% troughs). Regional variations in dominant forces influencing shoal formation and evolution were observed by the vertical classification of the shoal state. The West Shoal is river dominated, the East Shoal is tide dominated, and the Middle Shoal reflects an interaction between riverine inflows and tides. Stabilized curves observed between 2008 and 2018 indicate that this estuary is progressively achieving new equilibrium states. The depth–area spatial function is useful for identifying shoals and troughs within various estuaries, which also provides a geomorphological framework for understanding the estuarine evolution and sediment dynamics.

Functions and targets of miRNAs in pharmacological and toxicological effects of major components of Tripterygium wilfordii Hook F - Wei Pan; Bo Yang; Dongxiu He; Linxi Chen; Chengxiao Fu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2024)

A short neuropeptide F analog (sNPF), III-2 may particularly regulate juvenile hormone III to influence Spodoptera frugiperda metamorphosis and development - Wenjing Cao; Fu Zhang; Haolin Li; Yimeng Zhang; Yongheng Zhang; Wenjie Zhang; Xiaxia Guo; Linxi Dong; Honghong Li; Dongqiang Zeng; Xuesheng Li; Xinling Yang (Pesticide Biochemistry and Physiology, 2023)

S-dinotefuran affects the social behavior of honeybees (Apis mellifera)and increases their risk in the colony - Fu Zhang; Wenjing Cao; Yongheng Zhang; Jie Luo; Jiangan Hou; Lichao Chen; Guoqiang Yi; Honghong Li; Mingfeng Huang; Linxi Dong; Xuesheng Li (Pesticide Biochemistry and Physiology, 2023)

Responses of tidal duration asymmetry to morphological changes in Lingding Bay of the Pearl River Estuary - Qingshu Yang; Shuai Hu; Linxi Fu; Ping Zhang; Nanyang Chu; Feng Liu; Huayang Cai (Frontiers in Marine Science, 2022)
Tidal asymmetry is one of the main factors for generating net transport for waterborne materials in tidal estuaries, and thus, this phenomenon has significant influences on controlling morphological development and the ecological environment. Tidal propagation is sensitive to changes in the coastline and geometry of estuarine regions. Moreover, tidal waveforms vary with various factors, such as coastline changes and bathymetry evolution due to local anthropogenic activities. The topography of Lingding Bay (LDB) of the Pearl River Estuary (PRE) has greatly changed since the 1960s because of human interventions, but the response of tidal duration asymmetry (TDA) to morphological changes is still poorly understood. Utilizing the two-dimensional Delft-3D flexible mesh numerical model, the spatial pattern of TDA and its primary contributors in LDB of the PRE were reproduced for 1964, 1989, and 2016, accounting for the changes in both shoreline and bathymetry owing to human interventions. The results reveal that as the tidal wave propagates upstream, the tidal skewness increases from negative values to positive values longitudinally, indicating the transition from a shorter ebb-duration state to a shorter flood-duration state. Additionally, a prominent shift in TDA and its primary contributors takes place approximately in the period of 1989. In 1964-1989, the tidal skewness increased by at least 0.1 throughout the LDB, indicating that the flood duration of the entire bay was shortened significantly. However, in 1989-2016, the tidal skewness decreased by at most 0.15 throughout the LDB, representing a longer flood duration in the entire LDB. The scenario simulations reveal that reclamation-induced shoreline changes control the increase in TDA and its primary contributors by enhancing width convergence of estuary in the period of 1964-1989. Conversely, the increase in water depth plays a vital role in the decrease of TDA in the period of 1989-2016. The results obtained from this study are particularly useful for understanding the controlled factors contributing to net sediment transport and the associated long-term morphological evolution in estuaries heavily impacted by human interventions.

Distribution, Sources, and Biogeochemistry of Carbon Pools (DIC, DOC, and POC) in the Mangrove-Fringed Zhangjiang Estuary, China - Ran Yan; Jianxiang Feng; Yuming Wang; Linxi Fu; Xiangxin Luo; Lixia Niu; Qingshu Yang (Frontiers in Marine Science, 2022)
The lateral carbon export related to mangroves is of great scientific significance and ecological value in the global carbon cycle. The dissolved inorganic carbon (DIC), dissolved organic carbon (DOC), particulate organic carbon (POC), and stable isotopes (δ 13 C POC ) of water samples were quantified in the flood (September 2020) and dry (January 2021) seasons in Zhangjiang Estuary. The results revealed that the carbon compositions in the tidal channel of the Zhangjiang Estuary are as follows: DIC > DOC > POC in both seasons. Except for the POC in the site near the sluice, the contents of all carbon compositions were significantly larger in the flood season than those in the dry season (p< 0.05). In the flood season, the POC and DOC exhibited similar spatial characteristics that all sites from the lower sites to the mouth were significantly larger than the site near the sluice. The DIC had an increasing trend from the upper site to the mouth. In the dry season, DIC and DOC displayed patchy distribution under the influence of mariculture and the sluice, while the POC had a decreasing trend from the upper site to the mouth. The MixSIAR model indicates that the source of the POC is overwhelmingly the mariculture, averagely accounting for 42.7% in the flood season and 52.6% in the dry season, mainly in the form of microalgae. The average contribution of mangrove to POC was 33.1% in the flood season and 39.3% in the dry season. The DIC-δ 13 C POC and DOC-POC relationships represent the biogeochemical process of microbial photosynthesis and the physical process of adsorption-desorption of organic carbon by redundancy analysis, respectively. This initial dataset for this region should be included in other studies to improve the mangrove outwelling estimate.